Gaya Bahasa Lead Berita Pada Kanal Daerah Media RRI.Co.Id - Nisfah Dianti Mawaddah Harahap; Fani Nur Jannah (Program Studi Penerbitan, Politeknik Negeri Jakarta, 2024)
In today's digital era, online media has become the primary choice for the public to access information quickly and easily. These platforms offer a diverse range of content, from business and politics to technology and entertainment. News, as an informational product of online media, plays a crucial role in conveying facts and ideas that are engaging to the audience. According to Sumadiria (2016), news can be categorized into two types: hard news and soft news. The structure of news writing follows specific elements, including the headline, dateline, lead, body, and conclusion. The lead serves as an important summary that captures readers' interest and must address the 5W+1H questions (What, Who, When, Where, Why, and How).This study aims to analyze the application of language style in writing leads on the regional channel of rri.co.id Jakarta network. The methodology employed is descriptive, utilizing data collection techniques such as literature review, direct observation during an industry internship at Radio Republik Indonesia, and interviews with editorial staff. From the analysis of 10 news articles published in December 2023, it was found that only 20% of the leads met the concise criteria (30-45 words), while 80% exceeded this limit. The most frequently used elements were